Evaluation of behavior in veal calves fed milk containing different levels of hempseed cake (Cannabis sativa L.) - Arango, Sheyla; Guzzo, Nadia; Trabacchin, V.; Raffrenato, Emiliano; Sartori, Cristina; Bailoni, Lucia (Frontiers in Veterinary Science, 2023)
The present study aimed to evaluate the effect on behavioral patterns of veal calves fed with increasing levels of hempseed cake (HSC) diluted in the milk replacer. In total, 48 Belgian Blue veal calves (12 females and 36 males), with a body weight (BW) of 62.0 kg and age of 42.6 days, were offered the same type and quantity of solid and liquid feed two times a day but randomly assigned to one of the three different HSC inclusion levels: 0% (CTR), 3% (T3), and 6% (T6). The study lasted for 6 months until slaughter. During this time, their behavior was recorded using video cameras provided with a surveillance system. The results indicated that HSC had negligible effect on calves' behavior and that calves, in general, spend most of their time resting and ruminating as they normally do with conventional diets. Hempseed cake inclusion (T3 and T6) increased (P < 0.05) the appetite for solid food and licking behavior during the late afternoon. T3 female calves increased (P < 0.05) their movement in the late afternoon. Male calves decreased (P < 0.05) their positive interaction, movement, and cross-sucking in the late afternoon as the inclusion of HSC increased. The inclusion of HSC into veal calves' diet did not negatively affect the animal's behavior; therefore, it can be suggested as a novel ingredient.